Sharia Public Private Partnership: An Alternative Financing For Infrastructure Development In Indonesia - Arnoldy; Afried Lazuardi; Yulianti Yulianti; Muhammad Ichwan Hamzah (LP2M IAIN Palopo, 2025)
Infrastructure development in Indonesia requires diverse and sustainable sources of financing, because the Indonesian APBN/APBD is not sufficient to finance Indonesian infrastructure financing needs, so other alternative sources of financing are needed. The aim of this research is to examine the role of Sharia Public Private Partnership (Sharia PPP) as an alternative financing for infrastructure development in Indonesia. The research is qualitative research in the form of descriptive analysis through library research, literature and government policies/regulations. The research results show that regulatory the Sharia PPP has a legal basis and the government has provided support, facilities (by establishing financing and guarantee institutions) and incentives for PPP projects, however its implementation still faces obstacles in terms of institutional readiness, sharia financial literacy, sharia financing instruments, size Indonesia’s Islamic Bank asset as well as lack understanding of business entities and market players